2009
DOI: 10.2225/vol12-issue3-fulltext-10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of diversity among six populations of Colombian mango (Mangifera indica L. cvar. Hilacha) using RAPDs markers

Abstract: Abbreviations: AFLP: amplified fragment length polymorphism IDEA: Fundación Instituto de Estudios Avanzados (Venezuela) ISTR: inverse sequence tagged repeat NTSYSpc: numerical taxonomy and multivariate analysis system ver. 2.02j POPGENE: population genetic analysis ver. 1.32 RAPD: random amplified polymorphic DNA RFLP: restriction fragment length polymorphism SSRs: simple sequence repeats STRs: short tandem repeats TFPGA: tools for population genetic analyses ver.1.3 UPGMA: unweighted pair group method with ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Hilacha) stem bark were pulverised in a plant blender (Blendor, Warig Commercial) at a size range of 250 -300 mm before extraction.The bark has been collected from cultivated mango trees in Colombia from the production zone of Tolima, where Prof. Nicola Silvana (horticultural science) confirmed by morphological analysis the origin of the plant material. Previous studies confirmed a very little genetic differentiation among the Mango Hilacha populations in Tolima(Díaz-Matallana et al 2009). …”
mentioning
confidence: 79%
“…Hilacha) stem bark were pulverised in a plant blender (Blendor, Warig Commercial) at a size range of 250 -300 mm before extraction.The bark has been collected from cultivated mango trees in Colombia from the production zone of Tolima, where Prof. Nicola Silvana (horticultural science) confirmed by morphological analysis the origin of the plant material. Previous studies confirmed a very little genetic differentiation among the Mango Hilacha populations in Tolima(Díaz-Matallana et al 2009). …”
mentioning
confidence: 79%
“…Although a lack of accessible wild M. indica populations precludes investigations of a primary bottleneck associated with the initial domestication of mango, the recent and well‐documented history of mango's human‐mediated migration into new regions of the world provides an opportunity to determine whether the species experienced a secondary genetic bottleneck during successive founder events. Although many previous studies have provided insight into the molecular diversity and genetic structure of mango cultivars within specific regions, including Kenya (Sennhenn et al ., ), Myanmar (Hirano et al ., ), China (Luo et al ., ), Colombia (Diaz‐Matallana et al ., ), Brazil (Dos Santos Ribeiro et al ., ), Iran (Shamili et al ., ) and, especially, India (Ravishankar et al ., , ; Kumar et al ., ; Karihaloo et al ., ; Damodaran et al ., ; Vasugi et al ., ; Surapaneni et al ., ), only a handful have examined mango cultivars originating across a broad geographical range. Works by Schnell et al .…”
Section: Introductionmentioning
confidence: 99%
“…studies have been reported on the application of different molecular markers with different mango genotypes for genetic diversity analyses such as RAPD (Schnell et al 1995;López-Valenzuela et al 1997;Kumar et al 2001;Karihaloo et al 2003;Rahman et al 2007;Mansour et al 2008;Díaz-Matallana et al 2009;Mansour et al 2014;Ahmedand, Mohamed 2015;Rashed, Maklad 2016;Galal et al 2017;El-Sayed et al 2018;He et al 2021), AFLP (Kashkush et al 2001;Yamanaka et al 2006;Zhang et al 2014;Wang et al 2015;Dang, Chen 2017) and SSR (Duval et al 2005;Honsho et al 2005;Singh et al 2012;Tsai et al 2013;Azmat et al 2016;Lal et al 2017;Ajayi et al 2019;Razak et al 2019;Yamanaka et al 2019). The start codon targeted (SCoT) polymorphism is a simple and effective gene targeted marker technique based on the conserved region surrounding the translation codon ATG (Collard, Mackill 2009).…”
Section: Methodsmentioning
confidence: 99%